Growth Accounting Model in Indonesia - Tuti Eka Asmarani (Institute of Computer Science (IOCS), 2023)
Based on growth accounting model, economic growth can be approximated by capital accumulation, human capital, labor, and total factor productivity. In this study, total factor productivity as a residual. This study used World Bank Indicator data from 1990 to 2021. This study stated that capital and labor have positive impact to economic growth, although human capital has not impact to economic growth. Human capital has not impact in t period. This is because it needs lag to everyone in implement value from human capital investment.